Vulnerability of street children - Gómez, María Luisa; Sevilla, María de la Luz; Álvarez, Nelson (Acta Bioethica, 2008)
This article offers an analysis of 20 semi-directed, open interviews realized with street children in Mexico City, which includes diverse topics (Family, Violence, Sexuality, Obtaining Resources and Addictions) and considers two life stages (before abandoning the home and their life on the street). These groups live in an environment with conditions of vulnerability, where the satisfaction of basic necessities is the primary focus of their decision making, causing lack of future expectations. One of their behavior patterns is drug abuse, solvents being the most typical drug of choice. Their sexuality, acted out in conditions of vulnerability, gives rise to frequent unwanted pregnancies and genital infections. In this context, the reproductive health of these marginal groups will have to be considered.